2008
DOI: 10.1002/bit.21840
|View full text |Cite
|
Sign up to set email alerts
|

The fate of Pluronic F‐68 in chondrocytes and CHO cells

Abstract: The surfactant Pluronic F-68 (PF-68) is widely used in large-scale mammalian cell culture to protect cells from shear stress that arises from agitation and gas sparging. Several studies suggested that PF-68 is incorporated into the cell plasma membrane and could enter the cells, but without providing any direct evidence. The current study has examined this question for two cell types, one of pharmaceutical interest (CHO cells) and the other of biomedical interest (chondrocytes or cartilage cells). A fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…Adding further complexity to the question of the actual interaction of PF-68 with cells, Gigout et al (2008) utilized a fluorescent derivative to show that PF-68 is taken up by CHO cells up to 12 lg/10 6 cells. This amount of uptake does not vary in static versus agitated culture, and did not vary as a function of PF-68 concentration in the culture.…”
Section: Cell Damage From Spargingmentioning
confidence: 99%
“…Adding further complexity to the question of the actual interaction of PF-68 with cells, Gigout et al (2008) utilized a fluorescent derivative to show that PF-68 is taken up by CHO cells up to 12 lg/10 6 cells. This amount of uptake does not vary in static versus agitated culture, and did not vary as a function of PF-68 concentration in the culture.…”
Section: Cell Damage From Spargingmentioning
confidence: 99%
“…In consistence with the current results, we have previously shown that although F68 has increased osteo-, adipo-and chondrogenic differentiation of hTGSCs, F127 has no or little effect, indicating cell-lineage free effect of F68 on hTGSC differentiation (Dogan et al 2012). Pluronic F68 has been shown to increase cell membrane integrity, growth and attachment of fibroblast cells, stating the potential protective effect on plasma membrane (Gigout et al 2008). Although the exact mechanisms in which F68 increases neuro-and myogenic differentiation of human stem cells need to be explored, one possible explanation for the effects of pluronics might be the stabilization of the cell membrane during differentiation resulting in effective lineage transformation as cell membrane tension and surface area might direct cell fate and differentiation (McBeath et al 2004;Titushkin and Cho 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the fact that F68 can incorporate into bio-membranes and modify their structural and functional properties by altering the lipid composition. 32 An elevated unsaturated ratio is known to increase membrane fluidity, 33 which may generally promote cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%